Recurrence rate after absorbable tack fixation of mesh in laparoscopic incisional hernia repair. Issue 5 (19th February 2015) - Christoffersen, M. W.; Brandt, E.; Helgstrand, F.; Westen, M.; Rosenberg, J.; Kehlet, H.; Strandfelt, P.; Bisgaard, T.
<x xml:space="preserve">Abstract</x> Background The mesh fixation technique in laparoscopic incisional hernia repair may influence the rates of hernia recurrence and chronic pain. This study investigated the long‐term risk of recurrence and chronic pain in patients undergoing laparoscopic incisional hernia repair with either absorbable or non‐absorbable tacks for mesh fixation. Methods This was a nationwide consecutive cohort study based on data collected prospectively concerning perioperative information and clinical follow‐up. Patients undergoing primary, elective, laparoscopic incisional hernia repair with absorbable or non‐absorbable tack fixation during a 4‐year interval were included. Follow‐up was by a structured questionnaire regarding recurrence and chronic pain, supplemented by clinical examination, and CT when indicated. Recurrence was defined as either reoperation for recurrence or clinical/radiological recurrence. Results Of 1037 eligible patients, 84·9 per cent responded to the questionnaire, and 816 were included for analysis. The median observation time for the cohort was 40 (range 0–72) months. The cumulative recurrence‐free survival rate was 71·5 and 82·0 per cent after absorbable and non‐absorbable tack fixation respectively (P = 0·007). In multivariable analysis, the use of absorbable tacks was an independent risk factor for recurrence (hazard ratio 1·53, 95 per cent c.i. 1·11 to 2·09; P = 0·008). The rate of moderate or severe chronic pain was 15·3 and 16·1 per cent after absorbable and non‐absorbable tack fixation respectively (P = 0·765). Conclusion Absorbable tack fixation of the mesh was associated with a higher risk of recurrence than non‐absorbable tacks for laparoscopic mesh repair of incisional hernia, but did not influence chronic pain.